(446) Determining Investment Priority Ratings تحديد تصنيفات أولوية الاستثمار - El Tigi, Aziz El Din (معهد التخطيط القومى, 2024)
This study examines the process of determining investment priority ratings as a fundamental component of economic planning and resource allocation. It is based on the assumption that development strategies depend significantly on the ability to rank investment projects according to objective criteria that maximize both economic and social returns. The study explains that investment prioritization should not rely solely on financial profitability indicators. Instead, it requires broader evaluation measures capable of capturing both direct and indirect economic and social effects of investment projects. Within this context, the study discusses the Social Marginal Product (SMP) method as an analytical framework for improving resource allocation across competing sectors and projects by assessing their expected contributions to development objectives. Furthermore, the study addresses methods for calculating social returns on investment and emphasizes the importance of incorporating indirect impacts into evaluation processes. Such impacts may include employment generation, income distribution effects, productivity enhancement, and long-term economic growth outcomes. The study argues that project evaluation should therefore rely on an integrated set of economic and social indicators rather than a single financial measure. The document also reviews practical experiences derived from Turkey and the Philippines in establishing investment priorities. Particular attention is given to the use of questionnaires and applied assessment models designed to support decision-making and improve investment allocation procedures. The study concludes that effective investment planning requires the establishment of a comprehensive framework for evaluating and ranking investment alternatives. Such a framework contributes to efficient resource allocation and strengthens the ability of development policies to achieve sustainable economic and social objectives.